Descripción de la ansiedad estado rasgo y estrés laboral en colaboradores de algunas instituciones de salud en Boyacá (2021)
The objective of the research was: to describe the levels of trait state anxiety and work stress in collaborators of health institutions in Boyacá, a quantitative research with a non-experimental descriptive transectional design, empirical analytical approach, 60 collaborators were selected from three health institutions in Boyacá, from a clinic in Tunja 24 collaborators, from the ESE of Tasco 20 collaborators and from the ESE of Pesca 16 collaborators, for the evaluation a sociodemographic survey and two measurement instruments were used, the IDARE inventory to measure trait state anxiety and the inventory of mental health, stress and work SWS.